227k views
5 votes
Arrange the expressions in ascending order of their values when x = -2.

1-x^2/1-2x
x^2-1/1-2x
2x^2+x/2
3x^2+1/2(x-1)

1 Answer

3 votes

Explanation:

Option (1)


(1-x^2)/(1-2x)

Put x = -2, let the value is y such that,


y=(1-(-2)^2)/(1-2(-2))\\\\=(1-4)/(1+4)\\\\=-0.6

Option (2)


(x^2-1)/(1-2x)

Put x = -2, let the value is y such that,


y=((-2)^2-1)/(1-2(-2))\\\\=(4-1)/(1+4)\\\\=0.6

Option 3)


2x^2+(x)/(2)

Put x=-2 such that,


y=2(-2)^2+((-2))/(2)\\\\=7

Option (4)


3x^2+(1)/(2(x-1))

Put x =-2 such that,


y=3(-2)^2+(1)/(2((-2)-1))\\\\=11.83

Ascending values : -0.6,0.6,7,11.83

or


(1-x^2)/(1-2x) <
(x^2-1)/(1-2x) <
2x^2+(x)/(2) <
3x^2+(1)/(2(x-1))

User Kurochenko
by
4.8k points